2010
DOI: 10.1007/s10592-010-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and landscape genetic structure of otter (Lutra lutra) populations in Europe

Abstract: Eurasian otter populations strongly declined and partially disappeared due to global and local causes (habitat destruction, water pollution, human persecution) in parts of their continental range. Conservation strategies, based on reintroduction projects or restoration of dispersal corridors, should rely on sound knowledge of the historical or recent consequences of population genetic structuring. Here we present the results of a survey performed on 616 samples, collected from 19 European countries, genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
65
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 56 publications
12
65
2
Order By: Relevance
“…Although levels of heterozygosity in the three populations (H O = 0.56-0.57) were not high when compared with average heterozygosity across 74 studies of healthy placental mammal species (H O = 0.67 (Garner et al 2005)), they are not appreciably lower than levels reported in healthy mustelid populations (H O = 0.60 (Garner et al 2005)). When compared with other carnivores which are known to have undergone a population decline (Table 4), the giant otter appears to have maintained similar levels of genetic diversity to that found by Mucci et al (2010) in the Eurasian otter, and slightly higher than found in the heavily persecuted sea otter (Larson et al 2002). The high F IS values (0.09-0.19) and low N E (Table 3) recorded for each population do raise some concern for the viability of the remaining populations, since only the Essequibo population was found to have an N E of greater than 50.…”
Section: Discussionmentioning
confidence: 65%
“…Although levels of heterozygosity in the three populations (H O = 0.56-0.57) were not high when compared with average heterozygosity across 74 studies of healthy placental mammal species (H O = 0.67 (Garner et al 2005)), they are not appreciably lower than levels reported in healthy mustelid populations (H O = 0.60 (Garner et al 2005)). When compared with other carnivores which are known to have undergone a population decline (Table 4), the giant otter appears to have maintained similar levels of genetic diversity to that found by Mucci et al (2010) in the Eurasian otter, and slightly higher than found in the heavily persecuted sea otter (Larson et al 2002). The high F IS values (0.09-0.19) and low N E (Table 3) recorded for each population do raise some concern for the viability of the remaining populations, since only the Essequibo population was found to have an N E of greater than 50.…”
Section: Discussionmentioning
confidence: 65%
“…This is particularly important in Italy where the Eurasian otter shows the highest genetic differentiation among the European populations. This indicates that local adaptations might have developed there, and thus, Italian populations should be considered as an evolutionary significant unit (ESU) and should also be of special conservation interest due to their uniqueness (Randi et al 2003;Mucci et al 2010). The Eurasian otter is a suitable species for applying NGS due to the typical scat marking behaviour used for intra-specific communication (Chanin 1985;Gorman and Trowbridge 1989;Kruuk 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the fitness of Iberian otter populations can compromise future dispersal potential and prevent colonization of new areas that may become suitable after climate change (Cianfrani et al 2011). Additionally Mucci et al (2010) conducted a European wide otter molecular study and indicated that some local populations are genetically differentiated. Otters from Alentejo are included in the south cluster from Iberia that it is split into two sub-populations.…”
Section: Discussionmentioning
confidence: 99%